Use of murinometrics indices and bioelectrical impedance (BIA) in the determination of experimental obesity in oophorectomized rats (Acta Scientiarum. Biological Sciences, 2016)
In this study, we tested the use of murinometric indices and bioimpedance (BIA) to determine obesity in rats. Female Wistar rats (8 weeks/130-160 g) were divided into control and oophorectomy group. The Body Mass Index (BMI) and Lee index (LI) were used as anthropometric techniques to determine obesity, and the determination of body composition by BIA, as a way to partition body weight into fat mass and lean mass components. The dissection of muscle tissues and adipose deposits was used as a direct determination of body fat content. The groups had body weight gain (p